Analysis of Marketing Value Chain Development of Halal Food Products (Case Study of Kato Dehydrated Food Startup) - Sugeng Santoso; Rian Ubaidillah; Puji Aprilia; Yustus Odena Haloho; Khairunnisa Kahfi; Afifah Ayati; Wiwik Widyaningsih (Universitas Mercu Buana, 2021)
(The creative economy development policy, namely the development of economic activities based on individual creativity, skills, and talents to create individual creative and creative power that has economic value and affects the welfare of the Indonesian people. The creative economy, especially kato dehydrated food, displays creativity in the culinary field to offer food ingredients. both dried and ready-to-eat spices. The formulation of the problem is as follows: how is the development and innovation of the creative economy in the culinary field and what are the supporting and inhibiting factors in the development of the creative economy in the culinary field through the marketing mix (case study of Kato dehydrated food) ?. The results of this study are as follows: the existence of a creative economy based on drying dehydrated food kato food is sufficient to help the level of welfare and community needs. The marketing mix is the limitation of the creative economy development strategy carried out by Kato Dehydrated Foods, namely: products, prices, promotions and places / distribution channels. There are supporting factors, one of which is: The winner of the FSI who was awarded the ministry in 2020, and the other is also an inhibiting factor: Lack of public insight into the types of food ingredients that are dried in each dish.